A Method for Local Clock's Error With Kalman Filter Based on Mahalanobis Distance. Issue 1 (June 2020) - Chi, Xinghua; Zhu, Zhaohan; Dong, Zhouyang; Xu, Fenghui; Xu, Jian
Abstract: In order to improve the punctuality of local clock, it needs to use a proper filter to weaken the influence caused by noise in raw clock's error data. In this paper, An improved Kalman Filter based on Mahalanobis distance is proposed, and the process are shown in details. The final test shows the effectiveness of the improved method in estimation of local clock's error with gross error.